Corn and Palmer amaranth interactions in dryland and irrigated environments - Rule, Dwain Michael (Kansas State University, 2007)
Palmer amaranth is a competitive weed and has caused variable corn yield losses in diverse environments of Kansas. The objectives of this study were to 1) determine corn and Palmer amaranth growth, development, and grain (seed) production, 2) determine soil water content throughout the growing season, and 3) evaluate the performance of the modified ALMANAC model for simulating monoculture corn yield and corn yield loss from Palmer amaranth competition when corn and Palmer amaranth were grown alone or in competition under dryland and irrigated environments. For the first objective, field experiments were conducted in 2005 and 2006 with whole-plots of dryland and furrow irrigation arranged in a side-by-side design. Within each soil water environment, sub-plot treatments were monoculture Palmer amaranth at one plant m-1 of row, and corn with zero, one, and four Palmer amaranth plants m-1 of row. Corn height, leaf number, LAI, and total plant dry weight were reduced with increasing water stress and were reduced further in the presence of Palmer amaranth. Corn yield losses were similar with increasing Palmer amaranth density across soil water environments in each year, except for 2006 dryland corn. Palmer amaranth growth and development were negatively impacted by corn interference and weed density. For the second objective, Time Domain Reflectometry measurements documented seasonal trends of volumetric soil water content at the 0 to 15 and 0 to 30 cm soil profile depths for treatments in dryland and irrigated environments each year. The soil water depletion rate increased as water received prior to a drying period increased at the 0 to 30 cm soil depth in the dryland and irrigated environments. For the third objective, the modified ALMANAC model was parameterized based on monoculture corn and Palmer amaranth growth data. The model underestimated monoculture corn yield but overestimated corn yield with Palmer amaranth competition. The model performance was not consistent when comparing simulation results to dryland and irrigated experiments conducted across Kansas. Overall, the experiment provided an improved understanding of corn yield loss risks associated with water management and Palmer amaranth competition.
Keywords: Competition; Corn; Palmer amaranth; Crop model; Agriculture, Agronomy (0285)